Unraveling Aircraft Flutter: The Role of Structural Actuator Saturation in Aeroelastic Instabilities - Marcelo Santiago de Sousa; Luiz Felipi Ribeiro Siqueira; José Junior Leão Rodrigues; Flávio Luiz Cardoso-Ribeiro (Archives of Current Research International, 2024)
This article presents a new concept that can be used to explain the physical mechanism that causes flutter: the concept of the structural actuator and the effects of its saturation on the aeroelastic stability of an aircraft. One detailed physical mechanism that could be the cause of a flutter, that occurred during the numerical simulation of an aircraft, is presented. Each aeroelastic mode consists of torsional and rotational movements. These two movements in each mode were dissociated and the amplitude and phase of each movement were analyzed along with the damping and frequency of the mode. The structural resistances of torsion and bending, as well as the bending movement itself, have a damping effect and torsion has an destabilizing effect on the oscillations (if the centre of pressure is ahead of the flexural axis). After a certain speed, bending becomes out of phase with the applied forces. At this point, the bending has an amplifying effect on the oscillations and only the structural stiffness dampens the movement. From the speed at which the bending movement is out of phase with the applied aerodynamic loads, the damping of the mode decreases with speed, until flutter occurs. One possible physical explanation for this sudden change of phase in bending can be attributed to the structural uncapacity to follow the higher frequency movements demanded on the structure. The real movement has an rate lower than the commanded. This difference can cause an gain and phase variation, similar to ones that occurs in actuators of flight control surfaces when they arrive on the onset frequency. Considering the structural wings are seen as physical actuators that moves the aerodynamic surfaces, if the phase difference comes close to 180 deg, the bending becomes one destabilizing movement, that is amplified with the airspeed. This causes a decreasing on the damping ratio until the flutter occurs. This idea is detailed presented in this paper.